Birthing a Nation: Political Legitimacy and Health Policy in Hastings Kamuzu Banda's Malawi, 1962–1980. Issue 2 (3rd March 2020) - Messac, Luke
Abstract : Drawing upon archives in Malawi, the UK and the USA, this article explores the place of public-sector medicine in President Hastings Kamuzu Banda's ideology of social protection in post-colonial Malawi. In the midst of internecine strife with his cabinet soon after independence, Banda abandoned health-care user fees, provided free food to hospital inpatients and promised new medical facilities. Later, Banda disregarded international advisers by refusing to promote contraception. Though some commentators attributed this policy to Banda's conservatism, birth control also ran counter to his regime's carefully constructed symbolism of abundance. Malawi's government was not unique in opposing outside efforts at population control, but Banda's ideology, which invoked what anthropologists of the 1970s called 'wealth-in-people', made mass sterilisation and intrauterine device (IUD) campaigns particularly unacceptable. Banda also made grand displays of his government's new hospitals. While he would not devote significant domestic resources to health, he mobilised funds from external donors, particularly governments facing their own crises of legitimacy. This article, then, complicates the existing literature on health in Kamuzu Banda's Malawi. While Banda did not consider health a priority, his reliance on symbols of abundance, health and fertility left him vulnerable to critique and compelled him to direct a modicum of resources toward public sector health facilities and to keep care at those facilities free of charge.